Induced Trf2 deletion leads to aging vascular phenotype in mice associated with arterial telomere uncapping, senescence signaling, and oxidative stress. (February 2019) - Morgan, R. Garrett; Walker, Ashley E.; Trott, Daniel W.; Machin, Daniel R.; Henson, Grant D.; Reihl, Kelly D.; Cawthon, Richard M.; Denchi, Eros L.; Liu, Yu; Bloom, Samuel I.; Phuong, Tam T.; Richardson, Russell S.; et al.
Abstract: Age-related vascular dysfunction in large elastic and resistance arteries is associated with reductions in microvascular perfusion and elevations in blood pressure. Recent evidence indicates that telomere uncapping-induced senescence in vascular cells may be an important source of oxidative stress and vascular dysfunction in aging, but the causal relationship between these processes has yet to be elucidated. To test this important unexplored hypothesis, we measured arterial senescence signaling and oxidative stress, carotid and mesenteric artery endothelium-dependent vasodilatory capacity, markers of mesenteric microvascular perfusion and endothelial glycocalyx deterioration, and blood pressure in a novel mouse model of Cre-inducible whole body Trf2 deletion and telomere uncapping. Trf2 deletion led to a 320% increase in arterial senescence signaling ( P < .05). There was a concurrent 29% and 22% reduction in peak endothelium-dependent vasodilation in carotid and mesenteric arteries, respectively, as well as a 63% reduction in mesenteric microvascular endothelial glycocalyx thickness (all P ≤ .01). Mesenteric microvascular perfusion was reduced by 8% and systolic blood pressure was increased by 9% following Trf2 deletion (both P < .05). Trf2 deletion also led to a pro-oxidative arterial phenotype characterized by increased in NADPH oxidase gene expression; a 210% increase in superoxide levels that was partly dependent on NADPH oxidase activity; and an oxidative stress mediated reduction in carotid artery vasodilation (all P ≤ .05). Collectively, our findings demonstrate that induced Trf2 deletion leads to telomere uncapping, increased senescence signaling, and oxidative stress mediated functional impairments in the vasculature similar to those seen in human aging. Highlights: Evidence of causal link between telomere uncapping and vascular dysfunction. Supports observational link between arterial telomere uncapping and hypertension Demonstrate that Trf2 deletion leads to ROS-mediated endothelial dysfunction.